A continuidade da ruptura. Do Neoclássico ao Modernismo: Schinkel, Behrens e Mies - Hugo de Macedo e Silva Teixeira (2014)
This topic became of special interest for me when trying to understand the "why" and "how" aesthetic architectural styles changed, and, in particular, the Modern movement, many times associated to the word "rupture". Besides my personal bias towards the work of these three Architects: Schinkel, Behrens and Mies, they also provided some other compelling factors such as physical proximity, temporal continuity, and the relationships they created with each other, directly or indirectly. This work, sustained by some built and unbuilt project exemples, tries to prove that unlike one might think, there´s a firm line of continuity between Neoclassical and Modern Architecture.